Evaluating Hospital Information Systems (HIS) Quality Using the DeLone & McLean Models and TOE Framework - A Alsoukni, Ahmed Ali (Aljameai, 2026)
Abstract: There is no doubt that hospital information systems HIS have an important role in improving healthcare efficiency and decision-making, yet their evaluation in some developing and fragile country contexts, like Libya, remains almost limited, especially in public healthcare systems. Therefore, the aim of this study was to assess the quality of HIS at the Libyan hospital of Diabetes and Endocrinology by attempting to integrate the DeLone and McLean IS success model with the TOE framework. This case study adopted a quantitative study approach in which data were obtained from 44 healthcare professionals, administrators, and IT staff via a structured questionnaire consisting of 46 items. Some statistical analyses and regression-based path were conducted in order to assess the system performance dimensions and contextual influences. The results of the study indicated that while HIS provided substantial organizational benefits, particularly, in efficiency and decision support, system quality, service quality, and user satisfaction were only perceived as moderate. Technological and organizational factors significantly affected HIS performance, whereas environmental influences were almost limited. This study offers empirical evidence from Libya, confirms the relevance of established IS success models in developing healthcare settings, and provides practical recommendations for sustainable digital health development. المستخلص: لا شك أن نظم معلومات المستشفيات (HIS) تعتبر من اهم الأدوات الاساسية المستخدمة في تعزيز كفاءة الرعاية الصحية و التي من شأنها يمكن أن تؤدي إلى ودعم اتخاذ القرار، بالرغم من أن دراستها و تقييمها في سياقات الدول النامية والهشة، على سبيل المثال ليبيا، مازال يعتبر نسبيا محدودًا، و لا سيما في ظل وجود أنظمة الرعاية الصحية العامة. حيث كان الهدف من هذه الدراسة هو لتقييم جودة نظم معلومات المستشفيات في مستشفى السكري والغدد الصماء أبن النفيس, صلاح الدين بطرابلس، ليبيا، و ذلك من خلال استخدام نموذج نجاح نظم المعلومات المعروف ب DeLone McLean & و إطار التكنولوجيا المنظمة البيئة المعروف باسم .TOE حيث اعتمدت هذه الدراسة البحثية على استخدام منهجًا كميًا قائمًا على دراسة حالة، و تم جمع البيانات من 44 من الكوادر العاملين الصحيين والإداريين وموظفي تقنية المعلومات في المستشفى و ذلك عن طريق استخدام استبانة مُنظمة احتوت على 46 فقرة . ايضا تم استخدام التحليلات الإحصائية الوصفية وتحليل المسار القائم على الانحدار لتقييم أبعاد أداء النظام والتأثيرات السياقية. و اظهرت نتائج الدراسة أن نظم معلومات المستشفيات تحقق فوائد تنظيمية بشكل واضح و ملموس، و لا سيما فيما يتعلق بتحسين الكفاءة ودعم اتخاذ القرار، إلا إن مستويات جودة النظام وجودة الخدمات ورضا المستخدمين ظهرت بمستويات متوسطة. كما اوضحت تلك النتائج أن العوامل التكنولوجية والتنظيمية كان لها تأثير معنوي واضح في أداء نظم معلومات المستشفيات، في حين ظل تأثير العوامل البيئية محدودًا من منظور العاملين بالمستشفى. لذلك فأن هذه الدراسة يمكن أن تقدم دليلًا تجريبيًا من السياق الليبي، وتؤكد صلاحية و ملاءمة نماذج نجاح نظم المعلومات المعتمدة في بيئات الرعاية الصحية بالدول النامية، فضلا عن تقديم توصيات عملية لدعم التنمية المستدامة للصحة الرقمية.